2020
DOI: 10.26719/emhj.20.001
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic-related inequalities in self-rated health status in Kermanshah city, Islamic Republic of Iran: a decomposition analysis

Abstract: Background: Socioeconomic-related inequalities in health are a major public health challenge in both developed and developing countries. Little evidence is available on socioeconomic-related inequalities in health in different regions of the Islamic Republic of Iran. Aims: This study aimed to determine socioeconomic-related inequality in poor self-rated health in adults in Kermanshah city, western Islamic Republic of Iran. Methods: This cross-sectional study with stratified sampling obtained data on socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Surprisingly, our findings showed that there was no significant relationship between QOL score and demographic features such as sex, employment, and education level, while epidemiologic studies on evaluation of QOL related factors in Iran suggested that poor economic status and lower education level are the most important predictors of lower QOL in Iranian society [ 17 – 19 ]. Also, a study in western Iran showed that socioeconomic status, physical inactivity, chronic diseases and lack of health insurance coverage are the most influential factors that cause poor QOL [ 18 ]. A previous study has reported a significant negative correlation between female gender and lower educational level with the QOLIE score in epileptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, our findings showed that there was no significant relationship between QOL score and demographic features such as sex, employment, and education level, while epidemiologic studies on evaluation of QOL related factors in Iran suggested that poor economic status and lower education level are the most important predictors of lower QOL in Iranian society [ 17 – 19 ]. Also, a study in western Iran showed that socioeconomic status, physical inactivity, chronic diseases and lack of health insurance coverage are the most influential factors that cause poor QOL [ 18 ]. A previous study has reported a significant negative correlation between female gender and lower educational level with the QOLIE score in epileptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of poor HRQoL in Rezaei et al study (35.3 percent) was higher than the current study. They indicated that physical activity accounts for more than 14 percent of the inequality in the poor HRQoL (Rezaei et al, 2018). On the basis of these two studies, smoking has a low contribution in the inequality in poor HRQoL, but it should be noted that smoking has a reverse significant relationship with the people HRQoL (Rezaei, Karami Matin, Kazemi Karyani, Woldemichael, Khosravi, Khosravipour et al, 2017;Karyani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic and behavioral factors such as sex, age, physical activity and smoking are associated with the health status and HRQoL of people (Ramezani Doroh et al, 2015). Another study in Iran showed that more than 35 percent of general population have poor HRQoL, inequality in poor HRQoL is pro-poor and wealth, physical activity and chronic diseases are the main contributors of poor HRQoL (Rezaei et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the studies conducted on income-related inequality in health, SES has been reported as the most important contribution of pro-rich inequality in health. 39 , 40 We found no similar study for comparison. But one, by Emamian and colleagues, 41 reported that the concentration of the prevalence of risk factors of non-communicable diseases such as higher body mass index (BMI) was in the higher percentiles of economic rank of people.…”
Section: Discussionmentioning
confidence: 84%